DAMPAK ATRAKSI WISATA SAPARAN BEKAKAK BAGI MASYARAKAT DI KELURAHAN AMBARKETAWANG - , KURNIAWAN ODA HUTAMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bekakak Saparan ceremony is a ceremony that is of intangible to slaughter Bekakak Bride. Bekakak Saparan ceremony is held in the Ambarketawang village, Gamping.The event was held annually in the month of Safar between 10-20. The beginning of this Saparan Bekakak Ceremonyâs arrangements is to fulfill Dawuh Dalem Sri Sultan Hamengku Buwono I for remembering the service and loyalty of Abdi Dalem Ki Wirosuto who passed away mysteriously on following his duty to take care of the trace of Pesanggrahan Ambarketawang The beginning of this event are purposed to remember the service of AbdiDalem Ki Wirosuto, but in the journey of its ceremony the purpose are changed to be to keeping off of illness so that the public who work as stone neglect in Gunung Gamping are pushed away from accident. And now this ceremony prepared as a tourist attraction and potential cultural remain.